Geotechnical aspects of railway tunnel construction near rudoltice - Drusa, Marian; Grof, Vladimir (Communications - Scientific letters of the University of Zilina, 2004)
Construction of the tunnel in Trebovice v Cechach has been, from the geotechnical aspect, the most problematic issue ever, and, we would like to define some of the reasons and to sketch a potential solution.